Implementation of the Problem-Based Learning Model with a Multidisciplinary Approach in Enhancing Students' Critical Thinking Skills at SMP Al-Wasliyah 31 Medan - Hidayah, Cindy Nur; Amelia, Nisa; Putra, Alvino Dwi; Maulana, Hasbi (Yayasan Rahmat Islamiyah, 2025)
This research aims to determine the implementation of students' religious character development activities through Aqidah Akhlak learning. This research uses observation, interview and documentation data collection techniques. The research results show that the implementation of Aqidah Akhlak learning consists of opening activities, core activities and closing activities. The teacher uses a combination method consisting of lecture, question and answer, assignment and discussion methods. Religious character development through learning Aqidah Akhlak at MIN 4 Asahan is carried out using the example method, habituation and advice methods.